Permanent pacemaker implantation in Ebstein anomaly with metallic tricuspid valve - Doddaka, Nagabhushan; Vulli, Revanth; Agstam, Sourabh; Kadiyala, Vikas (International Journal of Advances in Medicine, 2021)
Right ventricular endocardial pacing is partially contraindicated in the presence of mechanical tricuspid valve. Occurrences of atrioventricular block are commonly associated in postoperative period in Ebstein anomaly repaired with mechanical tricuspid valve. Coronary sinus (CS) pacing is the preferred site in this scenario. However, the anatomical variations in Ebstein anomaly leads to difficulties in hooking the CS. With the help of real time left coronary injection enabled in understanding the anatomical orientation of CS ostium take off, leading to successful CS lead implantation.